Upper thermal tolerance differs between populations of a cyprinid fish, Pseudaspius sachalinensis - Taihei Yamada; Takaya Hatano; Daisuke Togaki; Yuya Kogame; Hirokazu Urabe (Journal of Fish Biology, 2026)
Understanding intraspecific variation in upper thermal tolerance is essential for assessing climate change impacts on freshwater fish communities. We experimentally evaluated thermal tolerance in a cyprinid fish, Pseudaspius sachalinensis , using critical thermal maximum (CT max ) measurements. Fish were collected from two tributaries in Hokkaido, Japan, differing in thermal variability but with similar mean temperatures. The population experiencing greater thermal fluctuations exhibited significantly higher CT max , whereas individual‐level factors (body size and condition) had no detectable effect. These findings highlight the importance of population‐specific conservation strategies under climate change.